HABITAT PREFERENCE OF SPANISH IBEX AND OTHER UNGULATES IN SIERRAS DE CAZORLA Y SEGURA (SPAIN) - ESCOS, J.; Alados, C. L. (MAMMALIA, 1992)
Studied the habitat preference in Autumn and Spring periods of Spanish ibex (Capra pyrenaica), fallow deer (Dama dama) and red deer (Cervus elaphus) in the Sierras de Cazorla y Segura Park (Spain). Spanish ibex occupied most altitude range studied, especially highest parts and avoiding areas below 800 m, red deer selected lowest elevations between 700 to 1100 m and fallow deer (between 1200-1600 m) occupied an intermediate annual altitudinal range. All the ungulates studied showed, except the red deer populations, a descent of altitudinal levels in the Spring period. Ibex used more covered areas specially females and young in Spring period, fallow deer occupied open habitats and red deer preferred holm-oak woods. In general terms the rut occurred in more open areas while in the birth season, females and young especially occupied covered areas. According to the overlap index (Pianka 1973) ibex with fallow deer could get a high risk of competition, while Spanish ibex and red deer, the only endemic species show the lowest level of overlapping on the resources studied. Segregation of the sexes studied in different habitats was observed. In Autumn, Spanish ibex and fallow deer showed a tendency to occupy sunny areas at dawn and dusk and this tendency occurred in red deer only at dawn but not at dusk. However in Spring, Spanish ibex, fallow and red deer occupied sunny slopes at dusk but only fallow deer do so at dawn.
The following values have no corresponding Zotero field: pub-location: 55 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: MUSEUM NAT HIST NATURELLE
Keywords: APS; Capra pyrenaica; cervus elaphus; Dama dama; habitat prefference; Holm oak; Spain; ungulates